Modalities of cosmopolitanism and mobility: parental education strategies of global, immigrant and local middle-class Israelis. Issue 5 (3rd September 2019) - Maxwell, Claire; Yemini, Miri
ABSTRACT: In this study, we explore how different forms of family mobility shape parental education strategies of three middle-class groups (moored Israeli professionals, immigrants from Israel to the UK and global middle class Israeli families). By focusing on families from the same nationality, we show how different practices of mobility differentiate between these middle-class fractions. Building on Andreotti's framework for 'global mindedness' we suggest that orientations to cosmopolitanism also differentiate between these groups – from tourism (moored middle class), to empathy (immigrant middle class), to visiting (global middle class). By drawing on this conceptualisation, it is possible to understand why, despite the considerable uncertainty that constant mobility generates for children's education and futures, global middle-class parents appear to assuredly navigate processes of securing and transmitting advantage.